The influences of financial self-efficacy and financial socialization on college students’ financial stress and coping - Kemnitz, Randy J. (Kansas State University, 2018)
There were 19.8 million college students in the U.S. in the fall of 2017 (NCES, 2017). These students face many challenges and opportunities including new social networks, enhanced academic pressures, new living arrangement and new financial responsibilities. Many of these students have had positive role models who have socialized them through discussion and example (Shim, Barber, Card, Xiao, & Serido, 2010). These role models may have instilled positive self-efficacy in these students as well helping to prepare the students for the many challenges and opportunities in college. Some students have not had those role models. This research seeks to understand the impact of positive socialization and self-efficacy on students’ feelings of financial stress and then on their choices of how to cope with that stress. The financial challenges of paying for college are well publicized with 44.2 million Americans currently owing over $1.48 trillion in student loan debt (NCES, 2017). In this study, the impact of these financial challenges is viewed through the lens of the Transactional Model of Stress and Coping Theory which proposes that stress is an individual perception influenced by that individual’s sense of threat, vulnerability, and ability to cope (Lazarus & Folkman, 1984). There are two sets of empirical models; the first examines the influences in the appraisal process on perceptions of financial stress using OLS regression with the second empirical model examining the influences on their coping choices using logistic regression. Both models control for influences on stress and coping choices including demographic, socio-economic and academic factors. The results inform how financial self-efficacy and financial socialization influence financial stress as they suggest the importance of enabling financial self-efficacy by parents, educators and other leaders of children.
Keywords: College Student Financial Stress